Effects of Technological Diffusion and Access to Electricity on Employment in Nigeria - Ubah, Jeremiah I.; Bowale, Ebenezer K.; Ejemeyovwi, Jeremiah O.; Okereke, Yvonne (International Journal of Energy Economics and Policy, 2021)
Demographic transitions and technological advancements may lead to a net loss of 5 million jobs by 2020; hence, about forty percent (1.4 billion) of the global workforce are vulnerable to unemployment. This is because a more significant percentage of tasks that are already being disrupted by automation are repetitive and standardized processes. At the same time, actions/jobs which require empathy, genuine creativity, and critical thinking will be in high demand in the new workforce, thereby achieving a human-machine collaboration. Thus, this study seeks to investigate the influence that technology has on employment in the Nigerian labor market and how Access to electricity and employment are connected using Nigeria as a case study. The unit root test was conducted via Phillip-Perron (PP) statistics and Augmented Dickey-Fuller (ADF) tests. The Auto-Regressive Distributed Lag (ARDL) model was also employed to evaluate the relationship between technology and employment in Nigeria using World Bank data (1960-2017). Results showed that technology and globalization have a long-run statistically significant inverse relationship with employment in Nigeria, which conforms to theory. Policy recommendations promote the acquisition of such skills encompassing critical thinking, empathy, and creativity to enable a better future for the Nigerian labor force. Keywords: Employment; Labor; Technology; Globalization; Nigeria. JEL Classifications: O14, E24, J21 DOI: https://doi.org/10.32479/ijeep.10231